Hubungan Sikap Diet Penurunan Berat Badan dan Pengetahuan Diet Terhadap Status Gizi Remaja Putri di Pondok Pesantren Asrama Rasydiyah Khalidiyah Amuntai Hulu Sungai Utara - Rosita Rosita; Rusman Efendi; Norhasanah Norhasanah; STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2013)
Teenage girls in Pondok Pesantren Rasydiyah Khalidiyah Amuntai Hulu Sungai Utara contained 21.42% of young women who go on a diet to gain weight , maintain weight 18.57% and 57.14% who lose weight posture is not too fat even there thin based on measurement results using the body mass index according to age (BMI / U) . This study aims to determine the correlation of dietary attitudes and knowledge of weight loss diet on the nutritional status of teenage girls in Pondok Pesantren Rasydiyah Khalidiyah Amuntai Hulu Sungai Utara . This study was an observational analytic with cross sectional design , the population is young women who totaled 272 people, sample in this study as many as 162 respondents with propotionate stratified random sampling technique . The analysis was performed by descriptive and statistical tests using Chi-Square . The results obtained there is a correlation between attitudes weight loss diet of the nutritional status of young women with p value <0.05 is 0.034 . Teenage girls with unfavorable attitudes diet weight loss diet as much as 90.6% of normal nutritional status . There is a correlation between knowledge of diet and nutritional status of teenage girls with p value <0.05 is 0.029 . The knowledge of diet high at 89.1% of normal nutritional status.